Molecular mechanism of PSMa3 aggregation: a new view - Tammara, Vaishnavi; Das, Atanu (Journal of Physical Chemistry B, 2023)
The emergence of a novel cross-alpha fibrillar structure, unlike the commonly observed sequence-independent cross-beta one, of a 22-residue bacterial virulent amphipathic alpha-helical peptide of the phenol soluble modulin (PSM) family, PSM alpha 3, with many deleterious effects on human life, has infused uncertainty to the paradigm of the intrinsically polymorphic, multivariate, multiphasic, and cross-sequence-cross-disease entangled protein aggregation landscape and hence on the identity of the therapeutic target. We, here, deconvolute the factors contributing to the genesis and hence the transition of lower to higher order aggregates of PSM alpha 3 in its natural state and three noncanonical designed variants using conventional and enhanced sampling approach-based atomistic simulations. PSM alpha 3 shows structural polymorphism with nominal alpha-helicity, substantial beta-propensity, and dominant random-coil features, irrespective of the extent of aggregation. Moreover, the individual features of the overall amphipathicity operate alternatively depending on the extent and organization of aggregation; the dominance gradually moves from charged to hydrophobic residues with the progressive generation of higher order aggregates (dimer to oligomer to fibril) and with increasing orderedness of the self-assembled construct (oligomer vs dimer/fibril). Similarly, the contribution of interchain salt bridges decreases with increasing order of aggregation (dimer to oligomer to fibril). However, the intrachain salt bridges consistently display their role in all phases of aggregation. Such phase-independent features also include equivalent roles of electrostatic and van der Waals forces on intrachain interactions, sole contribution of van der Waals forces on interchain cross-talk, and negligible peptide-water relationship. Finally, we propose a conjugate peptide-based aggregation suppressor having a single-point proline mutation.